2006
DOI: 10.1529/biophysj.105.074674
|View full text |Cite
|
Sign up to set email alerts
|

A Sticky Chain Model of the Elongation and Unfolding of Escherichia coli P Pili under Stress

Abstract: A model of the elongation of P pili expressed by uropathogenic Escherichia coli exposed to stress is presented. The model is based upon the sticky chain concept, which is based upon Hooke's law for elongation of the layer-to-layer and head-to-tail bonds between neighboring units in the PapA rod and a kinetic description of the opening and closing of bonds, described by rate equations and an energy landscape model. It provides an accurate description of the elongation behavior of P pili under stress and support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
105
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
1

Relationship

5
3

Authors

Journals

citations
Cited by 59 publications
(122 citation statements)
references
References 48 publications
12
105
1
Order By: Relevance
“…As for the later two phases, a sticky-chain model, which describes the stretched behaviors of a type 1 fimbria or a P fimbria (1,23), is suitable to describe the later two phases of a type 3 fimbria. Conceptually, in the uncoiling phase, closed layer-to-layer (LL) bonds in the helix-like structure of a type 3 fimbria are opened successively with the uncoiling force of 66 pN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the later two phases, a sticky-chain model, which describes the stretched behaviors of a type 1 fimbria or a P fimbria (1,23), is suitable to describe the later two phases of a type 3 fimbria. Conceptually, in the uncoiling phase, closed layer-to-layer (LL) bonds in the helix-like structure of a type 3 fimbria are opened successively with the uncoiling force of 66 pN.…”
Section: Discussionmentioning
confidence: 99%
“…In this phase, another particular stretching force of the fimbria occurs at the inflection point (x c ) of the S-shaped FEC, where the slope is minimal. This particular force is denoted the characteristic force (F ch ), which for P fimbriae is 67 pN (1).…”
mentioning
confidence: 99%
“…9 They have evolved into a three-dimensional helix-like structure, the PapA rod, [10][11][12][13][14] that can be successively and significantly elongated and/or unfolded when exposed to external forces. [13][14][15][16][17][18] The PapA rod is a thin micrometer-long helical rod composed of ~103 subunits that are coupled to their nearest neighbors by a β-strand complementation and combined in a right handed helical arrangement with 3.28 units per turn. [11][12][13][14] It has been hypothesized that the structure of the P pili, with its flexible structure and intricate unfolding mechanism, makes it possible for a UPEC bacterium to withstand considerable shear forces by a process in which a large number of pili can support tension simultaneously, despite dissimilar bacterium-to-host distances, 13,14 which, in turn, could explain why they can remain attached to the host tissue even in the presence of considerable urine flows.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14] However, because of the specific importance and unique behavior of E. coli P pili, their intrinsic mechanical properties were recently assessed using FMOT, both under conventional (steady-state) and dynamic modes of operation. [15][16][17][18] It was found that the PapA rod possesses a rich flavor of elongation and contraction behavior. For example, in addition to initial elastic stretching, the elongation of a P pilus takes place by a sequential and cooperative unfolding of its PapA rod.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggest that the quaternary structure of a fimbrial shaft plays an additional deterministic role in colonization, inasmuch as the shaft of certain ETEC fimbriae, as well as those of other pathogenic E. coli, is adapted to organ-specific biomechanical and structural features. Despite their differences in biogenesis and assembly processes, when analyzed biomechanically, ETEC-expressed fimbriae unwind at a characteristic low-unwinding steady force of Ͻ20 pN (7,8), while fimbriae expressed by extraintestinal pathogenic E. coli (ExPEC), such as type 1, P, and S fimbriae, require a steady force of Ͼ20 pN to unwind (7,(9)(10)(11)(12).…”
mentioning
confidence: 99%